Synaptosomal Mitochondrial Dysfunction in 5xFAD Mouse Model of Alzheimer's Disease - Wang, Lu; Guo, Lan; Lu, Lin; Sun, Huili; Shao, Muming; Beck, Simon J.; Li, Lin; Ramachandran, Janani; Du, Yifeng; Du, Heng (PLOS ONE, 2016)
Brain mitochondrial dysfunction is hallmark pathology of Alzheimer’s disease (AD). Recently, the role of synaptosomal mitochondrial dysfunction in the development of synaptic injury in AD has received increasing attention. Synaptosomal mitochondria are a subgroup of neuronal mitochondria specifically locating at synapses. They play an essential role in fueling synaptic functions by providing energy on the site; and their defects may lead to synaptic failure, which is an early and pronounced pathology in AD. In our previous studies we have determined early synaptosomal mitochondrial dysfunction in an AD animal model (J20 line) overexpressing human Amyloid beta (Aβ), the key mediator of AD. In view of the limitations of J20 line mice in representing the full aspects of amyloidopathy in AD cases, we employed 5xFAD mice which are thought to be a desirable paradigm of amyloidopathy as seen in AD subjects. In addition, we have also examined the status of synaptosomal mitochondrial dynamics as well as Parkin-mediated mitophagy which have not been previously investigated in this mouse model. In comparison to nontransgenic (nonTg mice), 5xFAD mice demonstrated prominent synaptosomal mitochondrial dysfunction. Moreover, synaptosomal mitochondria from the AD mouse model displayed imbalanced mitochondrial dynamics towards fission along with activated Parkin and LC3BII recruitment correlating to spatial learning & memory impairments in 5xFAD mice in an age-dependent manner. These results suggest that synaptosomal mitochondrial deficits are primary pathology in Aβ-rich environments and further confirm the relevance of synaptosomal mitochondrial deficits to the development of AD.